Pengembangan Perangkat Pembelajaran Berbasis TPACK pada Materi Sifat Koligatif Larutan untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Titin Mairisiska; Sutrisno Sutrisno; Asrial Asrial (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
TPACK based learning devices development research on the colligative properties is intended to develop Lesson Plan (RPP) and student’s activity sheets (LKS) in the form of a flip page ebook, apply the RPP and LKS and analyze the relationship among components of TPACK compiler. This research done by applying 4D Thiagarajan, Semmel and Semmel  Model, that has been modified. The results indicated on learning activities at the meeting I 92%, meeting II dan III 93,4%, meeting IV dan V 86,7%, meeting VI 86,1%, meeting VII 91,4%, all of them belong to the category of “highly optimized”. Students gave positive responses to the learning and products developed. The average percentage of student’s critical thinking skills as a whole is 66.3% which includes the category of “good”.